Futures trading of crude oil- a study on price risk management of crude oil futures - Prudha Mohan (College of co-operation, banking and management, 2008)
The study entitled “FUTURES TRADING OF CRUDE OIL – A STUDY ON PRICE RISK MANAGEMENT OF CRUDE OIL FUTURES” was undertaken to study the price movements in future prices of crude oil and price risk management in crude prices. The report first presents a summarization of the Indian commodity and crude futures and later it includes the description of Organization. The various concepts of futures trading are introduced later which gives a basic outline of different contracts undertaken, participants in futures market and various strategies followed. The study was based on secondary data. The information about the production, consumption, export and import of crude oil were collected from the website of Energy Information and Administration. This helped in studying the top producer, consumer, exporter and importer and their percentage share among top ten countries. The Multi Commodity Exchange traded crude oil futures data from 1 Jan to 31 Dec 2007 was used to undertake the study. The study analyses the trends in future prices by using least square method such as linear, parabolic and logarithmic trend. It revealed that the future prices showed more or less a parabolic trend. The movements in spot and future prices of crude oil were also analysed by finding the co – efficient of correlation and standard deviation. This study also examined the use of crude futures in hedging and risk reduction. It showed a positive correlation between the spot and future prices i.e. as the future prices increases the spot prices also increases. The project investigated methods involved in reducing the basis risk and the subsequent calculation of hedge ratio. The study brought out that the use of hedge ratios can reduce the basis risk to a considerable level. The hedging and the use of hedge ratio are an effective tool in price risk management. Thus futures trading play a very important role of performing economic function of price risk management.